2002
DOI: 10.1152/japplphysiol.01087.2001
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae gene expression changes during rotating wall vessel suspension culture

Abstract: This study utilizes Saccharomyces cerevisiae to study genetic responses to suspension culture. The suspension culture system used in this study is the high-aspect-ratio vessel, one type of the rotating wall vessel, that provides a high rate of gas exchange necessary for rapidly dividing cells. Cells were grown in the high-aspect-ratio vessel, and DNA microarray and metabolic analyses were used to determine the resulting changes in yeast gene expression. A significant number of genes were found to be up- or dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 41 publications
1
41
2
Order By: Relevance
“…A great deal of progress has been made in understanding certain aspects of microbial mechanotransduction, for example, mechanisms used by bacteria to respond to changes in osmotic gradients (7,40,85). Recently, studies have also documented that microbes can sense and respond to changes in culture conditions when grown in the buoyant, low-fluid-shear environment of microgravity (21,52,60,82). Moreover, it has been hypothesized that cells sense changes in mechanical forces, including shear and gravity, at their cell surface (48).…”
Section: Mechanosensitive Processes In Microorganismsmentioning
confidence: 99%
See 3 more Smart Citations
“…A great deal of progress has been made in understanding certain aspects of microbial mechanotransduction, for example, mechanisms used by bacteria to respond to changes in osmotic gradients (7,40,85). Recently, studies have also documented that microbes can sense and respond to changes in culture conditions when grown in the buoyant, low-fluid-shear environment of microgravity (21,52,60,82). Moreover, it has been hypothesized that cells sense changes in mechanical forces, including shear and gravity, at their cell surface (48).…”
Section: Mechanosensitive Processes In Microorganismsmentioning
confidence: 99%
“…Although it is true that the gravity force vector present in a liquid environment on Earth is very different in magnitude from that present in the space atmosphere, the low-shear buoyant sensation experienced in both environments is very similar. There is increasing evidence not only that entire organisms sense and respond physiologically to low-shear, buoyant environments but also that cells respond at the molecular level to this environment (43,52,81,106,107).…”
Section: Rotating-wall Vessel Culture Apparatus and The Low-shear Modmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been investigations into the effects of gravity on cells. With regard to low gravity, several studies have demonstrated that microgravity affects the regulation of gene expression in microorganisms, 1,2) but the effects of hypergravity have not been fully investigated for microorganisms, especially bacteria. In the fission yeast Schizosaccharomyces pombe, hypergravity produced by centrifugation stimulated marked activation of the stress-activated protein kinase pathway and the cell-integrity pathway.…”
Section: Inhibition Of Gene Expression In Escherichia Coli Under Hypementioning
confidence: 99%